A Potential Role of YAP/TAZ in the Interplay Between Metastasis and Metabolic Alterations - Yamaguchi, Hirohito; Taouk, Ghina M. (Frontiers in Oncology, 2020)
Yes-Associated Protein (YAP) and Transcriptional Co-activator with PDZ-binding Motif (TAZ) are the downstream effectors of the Hippo signaling pathway that play a crucial role in various aspects of cancer progression including metastasis. Metastasis is the multistep process of disseminating cancer cells in a body and responsible for the majority of cancer-related death. Emerging evidence has shown that cancer cells reprogram their metabolism to gain proliferation, invasion, migration, and anti-apoptotic abilities and adapt to various environment during metastasis. Moreover, it has increasingly been recognized that YAP/TAZ regulates cellular metabolism that is associated with the phenotypic changes, and recent studies suggest that the YAP/TAZ-mediated metabolic alterations contribute to metastasis. In this review, we will introduce the latest knowledge of YAP/TAZ regulation and function in cancer metastasis and metabolism, and discuss possible links between the YAP/TAZ-mediated metabolic reprogramming and metastasis.